2017
DOI: 10.3389/fvets.2017.00112
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cows Naturally Infected with Bovine Leukemia Virus Exhibit Abnormal B- and T-Cell Phenotypes after Primary and Secondary Exposures to Keyhole Limpet Hemocyanin

Abstract: Bovine leukemia virus (BLV) is a retrovirus that is highly prevalent in US dairy herds: over 83% are BLV infected and the within-herd infection rate can be almost 50% on average. While BLV is known to cause lymphosarcomas, only 5% or fewer infected cattle will develop lymphoma; this low prevalence of cancer has historically not been a concern to dairy producers. However, more recent research has found that BLV+ cows without lymphoma produce less milk and have shorter lifespans than uninfected herdmates. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
(48 reference statements)
3
18
1
2
Order By: Relevance
“…Indeed, BLV primarily infects B-cells (Meiron et al, 1997) and 66% of CD5 + B-cells carried the provirus (Mirsky et al, 1996). So, as others authors suggested (Frie et al, 2017), our results could indicate that infected B-cells proliferate in response to immune stimulation. A key factor to be taken into account is BLV reactivation when infected cell are in vitro cultured (Florins et al, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, BLV primarily infects B-cells (Meiron et al, 1997) and 66% of CD5 + B-cells carried the provirus (Mirsky et al, 1996). So, as others authors suggested (Frie et al, 2017), our results could indicate that infected B-cells proliferate in response to immune stimulation. A key factor to be taken into account is BLV reactivation when infected cell are in vitro cultured (Florins et al, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…In another series of studies, the authors suggested that the alteration in antibody production could be due to abnormalities in both B-and T-cell subsets also described in BLV+ cows (Frie et al, 2016(Frie et al, , 2017. Different outcomes observed in these studies, regarding which particular immune component was affected by BLV infection, might be explained either (1) the vaccine composition (antigen/immunogen), (2) the type of pathogens targeted by the vaccine (virus/bacteria), (3) the physiological status of the animals, (4) the relationship between the occurrence of BLV infection and the timing of vaccination (prime/boost), or (5) the number and timing of booster vaccination.…”
Section: Short Communication: Bovine Leukemia Virus Infection In Adulmentioning
confidence: 97%
“…Recent studies suggested that BLV infection might negatively affect animal immunity (Frie and Coussens, 2015). In this regard, 3 separate studies showed that immunological disorders provoked during BLV natural infection may counteract the development of immunity after commercial and experimental vaccination (Erskine et al, 2011;Frie et al, 2016;Puentes et al, 2016;Frie et al, 2017). Considering that BLV is endemic in many countries and approximately 50 to 70% of animals are asymptomatic, it is important to know whether BLV infection interferes with the immunogenicity elicited by those vaccines typically used in bovines, particularly those that are part of national programs.…”
Section: Short Communicationmentioning
confidence: 99%
“…El virus afecta células de la línea linfoide, principalmente los linfocitos B CD5+ que expresan inmunoglobulina M en su superficie, además de monocitos y macrófagos (OIE, 2012). El 90% de los animales infectados son asintomáticos, produciendo pérdidas productivas asociadas principalmente a la dificultad de exportación de animales en pie, disminución de la producción láctea como también la longevidad del animal y desregulación a nivel inmunológico (Erskine et al, 2011;Souza et al, 2012;Bartlett et al, 2013, Della Libera et al, 2015Frie et al, 2016, Puentes et al, 2016bFrie et al, 2017). Se ha demostrado que la infección subclínica por este virus causa disfunciones importantes del sistema inmune que impactan directamente en la sanidad (Bartlett et al, 2014), como por ejemplo disminución de la función de los polimorfonucleares in vitro inducido por Escherichia coli (E. coli) en vacas infectadas (Souza et al, 2012).…”
Section: Introductionunclassified
“…Las células T infectadas con el virus, expresan mayor cantidad de receptores inmunoinhibitorios, lo que aumenta la habilidad de los patógenos que causan infecciones crónicas a evadir la respuesta inmune del hospedador, aumentando por ejemplo la expresión de IL-10 o disminuyendo la de IL2, IL12 e IFN-γ (Konnai et al, 2003;Amills et al, 2004). Estas alteraciones del sistema inmune, destacados con mayor magnitud en animales con linfocitosis persistente podrían tener un impacto negativo en la capacidad de ganado para resistir al avance de la enfermedad infecciosa o a la respuesta a vacunas; en este mismo sentido algunos estudios reportaron una correlación positiva entre BLV y otras enfermedades (Emanuelson et al, 1992;Trainin et al, 1996) o cuestionan la habilidad de bovinos infectados con BLV para responder inmunológicamente contra otros patógenos (Erskine et al, 2011;Puentes et al, 2016b;Frie et al, 2016;Frie et al, 2017). Las enfermedades clostridiales constituyen una amenaza constante en la cría de ganado bovino, causando diversas afecciones como "mancha", "gangrena gaseosa", enterotoxemias, hemoglobinuria bacilar, hepatitis necrótica, tétanos y botulismo.…”
Section: Introductionunclassified